2021
DOI: 10.1177/1359104521994627
|View full text |Cite
|
Sign up to set email alerts
|

Sensation seeking and nonsuicidal self-injurious behavior among adolescent psychiatric patients

Abstract: The Benefits and Barriers model of NSSI postulates that engagement in NSSI is positively reinforced by potent benefits, however there are a host of barriers to engagement, any one of which is salient enough to prevent engagement. It is possible that individual differences in sensation seeking, a trait that describes optimal level of positive reinforcement, may alter the balance between the benefits and barriers of engagement in NSSI. There are significant associations between engagement in NSSI and sensation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
(61 reference statements)
1
8
1
Order By: Relevance
“…These findings were in alignment with a prior study that found that sensation seeking magnified the association between a risk factor (cyberbullying victimization) and adolescent NSSI [32]. According to the sensation seeking theory [49,50], individuals who seek high sensation also tend to enjoy novel experiences and taking risks, which in turn increases the possibility that they will use a risky behavior such as NSSI to escape depression [51]. Thus, for adolescents with high levels of sensation seeking, the relation between depression and NSSI became stronger.…”
Section: The Moderating Role Of Sensation Seekingsupporting
confidence: 87%
“…These findings were in alignment with a prior study that found that sensation seeking magnified the association between a risk factor (cyberbullying victimization) and adolescent NSSI [32]. According to the sensation seeking theory [49,50], individuals who seek high sensation also tend to enjoy novel experiences and taking risks, which in turn increases the possibility that they will use a risky behavior such as NSSI to escape depression [51]. Thus, for adolescents with high levels of sensation seeking, the relation between depression and NSSI became stronger.…”
Section: The Moderating Role Of Sensation Seekingsupporting
confidence: 87%
“…Moreover, the association between openness and NSSI was still significant when adjusting for sensation seeking. These findings are somewhat inconsistent with theories of NSSI that posit that one function of NSSI is sensation seeking (i.e., automatic positive reinforcement; Klonsky, 2007; Nock & Prinstein, 2004), but do fit with the mixed association between trait sensation seeking and NSSI (e.g., Glenn & Klonsky, 2010; Kentopp et al, 2021).…”
Section: Discussioncontrasting
confidence: 69%
“…Two relevant personality traits are sensation seeking and openness to experience. Sensation seeking (i.e., the propensity toward new experiences and sensations; Whiteside & Lynam, 2001) is a facet of impulsivity with mixed association with NSSI (Glenn & Klonsky, 2010; Kentopp et al, 2021). In trait models of personality, sensation seeking is seen as a facet of extraversion (Cyders & Smith, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Sensation seeking was measured using the Chinese version of the sensation seeking scale. These variables have all been shown to be associated with risk of NSSI ( 52 , 53 ).…”
Section: Methodsmentioning
confidence: 99%